(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper presents a numerical and experimental study of tidal rotors in regular waves. The study is based on an experimental campaign performed in a towing tank of two side-by-side axial flow rotors. The two turbines were towed in steady and regular wave conditions. Simulations were performed to mimic the experiments using a Reynolds-Averaged Navier-Stokes computational fluid dynamics model with a k-ω SST turbulence closure model, a Volume of Fluid model of the free surface, and an actuator line representation of the rotor. The model is compared to the towing tank experiments in terms of integrated thrust and power, blade root bending moments, and blade and wave phases. The numerical model shows good agreement with the experiments, capturing the magnitude of steady-state and dynamic loads, power performance, and root bending moments, although with discrepancies observed in wave-load phases. Only a very modest impact of waves on mean thrust and power is observed, however and in agreement with literature, waves induce substantial thrust and power fluctuations. The numerical model predicts that waves affect wake development, with more mixing and a faster recovery of kinetic energy downstream due to wave effects.